مساهمة سلوكات القيادة الأخلاقية في تعزيز الاستغراق الوظيفي للعاملين "دراسة ميدانية لعينة من المؤسسات الصحية" - لعموري فتحي (Universty Of El-oued جامعة الوادي, 2024)
هدفت هذه الدراسة إلى البحث في مساهمة سلوكات القيادة الأخلاقية بأبعادها (التوجه نحو الأفراد، العدالة، مشاركة السلطة، الاهتمام بالاستدامة، التوجيه الأخلاقي، توضيح الدور، النزاهة) في تعزيز الاستغراق الوظيفي للعاملين بأبعاده (الحماس، التفاني، الانغماس) وذلك في المؤسسات العمومية للصحة لولايتي الوادي والمغير والبالغ عددها 12 مؤسسة صحية، وتم الاعتماد في ذلك على المنهج الوصفي التحليلي من خلال الاعتماد على الاستبانة والمقابلة في جمع البيانات من عينة الدراسة التي تمثلت في 370 من العاملين في المؤسسات العمومية للصحة، حيث تم الاعتماد في تحليل البيانات على برنامج SPSS V25 من خلال العديد من الاختبارات الإحصائية، ومن خلال تحليل البيانات تم التوصل الى أن هناك مستوى متوسطا من ممارسة نمط القيادة الأخلاقية، كما أن هناك مستوى مرتفعا من الاستغراق الوظيفي بالمؤسسات محل الدراسة، كما تم التوصل الى وجود أثر ذو دلالة إحصائية للقيادة الأخلاقية على الاستغراق الوظيفي للعاملين، كما أظهرت النتائج كذلك أنه لا توجد فروق ذات دلالة احصائية في تصورات أفراد عينة الدراسة حول مستوى ممارسة المسؤولين في المؤسسات الصحية للقيادة الأخلاقية تعزى لمتغير الجنس، العمر وسنوات الخبرة، بينما يوجد فروق ذات دلالة احصائية في تصورات أفراد عينة الدراسة حول مستوى ممارسة المسؤولين في المؤسسات الصحية للقيادة الأخلاقية تعزى لمتغير المستوى الوظيفي، بالإضافة الى عدم وجود فروق ذات دلالة احصائية في تصورات أفراد عينة الدراسة لمستوى استغراقهم الوظيفي تعزى لمتغير الجنس، بينما هناك فروق ذات دلالة احصائية في تصورات أفراد عينة الدراسة لمستوى استغراقهم الوظيفي تعزى لمتغير العمر، المستوى الوظيفي وسنوات الخبرة. Résumé : فرنسية أو انجلزية This study aimed to explore the contribution of the ethical leadership in their dimensions (Fairness, People orientation, Power sharing, Concern for sustainability, Ethical guidance, Role clarification and Integrity) in enhancing the employee engagement in its dimensions (Vigor, Dedication, Absorption) in 12 public health institutions of the wilayas of El oued and El meghaier, and this was based on the descriptive analytical approach by relying on the questionnaire and interview in collecting data from the study sample, which was represented by 370 employees in public health institutions, the data analysis was based on the SPSS V25 Through many statistical tests, after data analysis, it was found that there is an average level of practicing ethical leadership style and employee engagement in the institutions under study, and it was also found that there is a statistically significant effect of ethical leadership on the employee engagement, and the results also showed that there are no statistically significant differences in the perceptions of the study sample members about the level of practice of officials in health institutions for ethical leadership due to the variable of gender, age and years of experience, while There are statistically significant differences in the perceptions of the study sample members about the level of practice of ethical leadership by officials in health institutions due to the functional level variable, in addition to the absence of statistically significant differences in the perceptions of the study sample members of the level of their engagement due to the gender and career level variable, while there are statistically significant differences in the perceptions of the study sample members of the level of their engagement due to the variable of age and years of experience.
أطروحة دكتوراه تخصص: تسيير الموارد البشرية في العلوم الاقتصادية و التجارية وعلوم التسيير
Keywords: قيادة، أخلاق، قيادة أخلاقية، استغراق وظيفي، مؤسسات صحية.; Ethics; Ledership; Ethical leadership; Employee engagement; Health institutions..